Cephalometric assessment of the hyoid bone position in Oral Breathing Children - Ferraz, Maria Julia Pereira Coelho [UNESP] (2007)
Material and Methods: because of its anatomical and functional relationship with the craniofacial complex, we assessed the cephalometry of the hyoid bone position in relation to the respiratory pattern of these 53 female children, with average age of 10 years; 28 of them are nasal breathers and 25 are oral breathers. Horizontal, vertical and angular cephalometric measures were used in order to determine the hyoid bone location. The Student t and the Pearson correlation tests were used in order to compare the groups and the variables. Results:We did not see statistically significant differences in mandible and hyoid bone positions and the respiratory pattern. In the hyoid triangle, the 0.40 correlation coeficient was significant between AA-ENP (distance between the Atlas vertebrae and the posterior nasal spine) and C3-H (distance between the third cervical vertebrae and the hyoid bone) showing a positive relation between the bony limits of the upper and lower air spaces. For cranial measures we have suggested a relationship between the hyoid bone position and the mandible morphology.Conclusion: The results led us o conclude that the hyoid bone keeps a stable position, probably in order to secure correct ratios in the airways, and it does not depend on the respiratory pattern. 1933 / 2007 © - Associação Brasileira de Otorrinolaringologia e Cirurgia Cérvico Facial. All rights reserved.